CLINICAL EFFICACY AND PECULIARITY OF COMPLIANCE WITH 48-WEEK LONG THERAPY WITH EGILOK RETARD IN PATIENTS WITH MILD TO MODERATE HYPERTENSION - V. E. Oleynikov; V. A. Budanova; A. V. Kulucin (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study antihypertensive efficacy of long-acting metoprolol, its influence on heart rate variability and therapy compliance in hypertensive patients during long-term (48 weeks) treatment. Material and Methods. After 2 weeks of wash-out period 30 hypertensive patients were prescribed long-acting metoprolol (Egilok Retard, EGIS) in dose of 50-100 mg once daily. If necessary the dose was increased up to 200 mg daily on 2 or 8 week, and on 12-16 weeks hydrochlorothiazide 12,5-25 mg daily and then nifedipine 20 mg daily were added. Ambulatory blood pressure monitoring (ABPM) and daily ECG monitoring were applied on 24 and 48 weeks. Patient quality of life was estimated. Results. In 48 weeks 22 patients (73,3%) continued the treatment. 5 patients dropped out because of low compliance and 3 patients because of low efficacy. Therapy discontinuation because of side effects was necessary in no one case. Monotherapy with metoprolol provided excellent results in 15 (68%) and combined therapy - in 7 (32%) patients. In comparison with starting data on 48 week of treatment significant reduction in 24-hour , day and night systolic blood pressure (BP) was registered on 10,4±1,6; 11,3±1,7 and 5,2±1,9 mm Hg, respectively, as well as diastolic BP on 7,7±1,1; 8,1±1,3 and 4,1±1,3 mm Hg, respectively. Time index of hypertension for 24-hour systolic and diastolic BP decreased significantly. Daily BP profile normalized. Normalization of BP and heart rate variability was observed among patients with its initial disturbances. The frequency of hypertensive symptoms such as headache and dizziness reduced on 58% and 64%, respectively. Capacity for work improved significantly. Conclusion. Long-acting metoprolol is effective antihypertensive medicine providing high level of compliance with long-term therapy.  Long-acting metoprolol is especially indicated to hypertensive patients with sympathetic system overactivity.